An Exploration of the Marital and Life Satisfactions of Middle-Aged Husbands and Wives - Abrioux, Marie-Louise; Zingle, Harvey W. (Canadian Journal of Counselling and Psychotherapy, 2012)
This study was designed to investigate attitudes concerning marital perceptions and life satisfaction of middle-aged husbands and wives who were in one of two periods of life. Couples in the postparental period were considered to be those who had launched all their children from the home, while couples in the parental period were considered to be those who still had some children in the home. A total of 160 subjects, that is, 80 couples were identified from two sources of intact marriages in the city of Edmonton. Forty of these couples constituted a counselled (C) sample ofmiddle-aged couples who were engaged in marital or family counselling at the time of this investigation. The noncounselled (NC) sample was comprised of 40 middle-aged couples who were not receiving counselling. A modified version of the Middle Years Life Satisfaction Scale (MYLSS), designed by Stinnett and Hayes (1971) was used to measure life satisfaction and the Middle Years Marital Perception Scale (MYMPS), which was based on an older person's perception scale, designed by Stinnett, Carter and Montgomery (1972), was used to obtain background information from the subjects and to investigate their perceptions of marriage. The results of the study ndicated that the NC and C samples of middle-aged couples were significantly different from one another with respect to life and marital satisfaction but that they were very similar in other respects, particularly in their reactions to the launching of the last child from the home. Certain qualities that were characteristic of being middle aged also became apparent.